Airline Service Quality in South Africa and Malaysia- An International Customer Expectations Approach - de, Johan W (Journal of Economics and Behavioral Studies, 2013)
This study attempts to identify the various service and value factors that matter most to domestic airline passengers in South Africa and to benchmark it with the domestic airline industry in Malaysia that has similar airline services. A survey methodology involving face-to-face interviews was employed to conduct interviews with 196 participants from South Africa and 189 from Malaysia. Respondents were targeted on a convenience basis. Despite the use of this non-probabilistic sampling method, the data that were yielded showed high levels of internal consistency. A random splitting of each of the two datasets (i.e. South Africa and Malaysia) and subsequent comparison of firstly, demographic characteristics and secondly, the average ratings of key items revealed no significant differences, thus confirming repeatability or reproducibility of measurement. Trained fieldworkers assisted with the interviews. The findings revealed the following. The first research objective identifies those aspects that respondents typically consider most and least important when travelling on a domestic airline. The mean importance ratings obtained for each of the service items were calculated and ranked from highest to lowest scores. The items were ranked within the four broader service dimensions for the two samples. The first dimension is labelled â€˜convenience of bookingâ€™ and the results reveal considerable similarities between the two samples, with both South African and Malaysian respondents rating online booking opportunity as the most important aspect within these dimensions. The second service dimension investigated in the study is â€˜cabin service scapesâ€™. The item that was rated most important by both South African and Malaysian respondents was comforts of the seats. The third service dimension labelled â€˜cabin crewâ€™. Cabin crew’s credibility obtained the highest average importance rating. The last dimension studied was labelled â€˜timeliness of flightâ€™. The top rated item was on-time departures and arrivals.